Biomimetic Leadership: Core Beliefs for Sustainable Organizations - Somoza-Norton, Andrea; Rivera Cárdenas, Claudia; Pabigian, Lisa; Drap, Megan (Journal of Ecohumanism, 2023)
Biomimetics is the science of applying nature-inspired designs and processes to human engineering and social innovation in order to solve complex problems. Emulating life’s blueprints and patterns, chemical processes, and ecosystem strategies leads to sustainable and regenerative solutions for a biosphere able to support all life on our planet. In a similar vein, Biomimetic Leadership encourages western 21st century leaders to rediscover the value of nature, apply life’s design principles, and utilize biomimetic thinking for the sake of improving organizations. Four core beliefs—Respect, Relate, Reflect, and Replicate—provide the foundation for Biomimetic Leadership as a new type of leadership. Each belief is a source of inspiration and offers insights into a hands-on approach to leading in an era of unprecedented environmental and economic concerns. Educating leaders for Biomimetic Leadership is a challenge that must be addressed by organizations with the objective of reaching equality, and by doing so, focusing on incorporating the four core beliefs described in this paper.